The open-air life eaudiobook Discover the nordic art of friluftsliv and embrace nature every day. - Åkeson Mcgurk, Linda (Penguin Audio, 2022)
A complete guide to Friluftsliv, the Nordic secret to unplugging and connecting more deeply with nature. In The Open-Air Life , Swedish-American writer Linda McGurk introduces readers to a wide array of Nordic customs and practices that focus on slowing down and spending more and more of ones’ time outdoors. An outdoorsy cousin of hygge , friluftsliv is what Nordic people do outside all day before they cozy up in front of the fireplace with their wool socks on and a cup of hot cocoa.   From the pleasures of foraging for wild berries and birding to how to stay warm and cozy outside in the middle of winter, this inspirational guide shows readers how to harness the power-of-nature to improve their physical and mental health, as well as their relationships with both other people and Mother Nature. Listeners will learn:   Why and how they should spend more time outside How to use friluftsliv to combat stress, anxiety disorders, depression, and burnout Practical skills like making fire, cooking outdoors and cleaning water on the go.    For country and city lovers alike, this audiobook will serve as an essential guide to slowing down in this modern, fast paced society and connecting with the natural world.